2017
DOI: 10.1103/physreve.96.012501
|View full text |Cite
|
Sign up to set email alerts
|

Marginally compact fractal trees with semiflexibility

Abstract: We study marginally compact macromolecular trees that are created by means of two different fractal generators. In doing so, we assume Gaussian statistics for the vectors connecting nodes of the trees. Moreover, we introduce bond-bond correlations that make the trees locally semiflexible. The symmetry of the structures allows an iterative construction of full sets of eigenmodes (notwithstanding the additional interactions that are present due to semiflexibility constraints), enabling us to get physical insight… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 66 publications
(161 reference statements)
0
4
0
Order By: Relevance
“…Recent simulation studies have suggested that other molecular architectures than linear chains may have mass scaling exponents governing polymer size (e.g., Rnormalg), less than ν=1/2. For randomly branched polymers in their melt state, ν has been proposed to be exactly 1/3 [55,56,57,58], indicating that these polymers also form rather ‘compact’ structures in the melt state [59]. Ring polymers in the melt have been predicted to exhibit this same type of asymptotic scaling [52], strongly suggesting that these polymers belong to the randomly branched polymer universality class when they are in the melt state.…”
Section: Resultsmentioning
confidence: 99%
“…Recent simulation studies have suggested that other molecular architectures than linear chains may have mass scaling exponents governing polymer size (e.g., Rnormalg), less than ν=1/2. For randomly branched polymers in their melt state, ν has been proposed to be exactly 1/3 [55,56,57,58], indicating that these polymers also form rather ‘compact’ structures in the melt state [59]. Ring polymers in the melt have been predicted to exhibit this same type of asymptotic scaling [52], strongly suggesting that these polymers belong to the randomly branched polymer universality class when they are in the melt state.…”
Section: Resultsmentioning
confidence: 99%
“…Randomly branched polymers in their melt state likewise exhibit a reduction in their mass scaling exponent ν due to the excluded volume screening. Recent simulation studies have suggested that ν for randomly branched polymers in their melt state is exactly 1/3, [43][44][45][46] indicating that these polymers form rather 'compact' structures in the melt state, rather than being like randomly branched polymers at their θ-point. Screening evidently operates differently between linear chains and randomly branched polymers.…”
Section: Background On Universality Classes Of Polymers In Relatimentioning
confidence: 99%
“…In particular, the resulting Gaussian networks [33][34][35] with (m, k)depending rigidities are often used for the description of 3D structures of proteins. In [36,37] static and dynamic properties of marginally compact trees with various fractal architectures were considered. A related hierarchical variational approach for an account of volume interactions of swollen polymer chains had been proposed in Ref.…”
Section: Fractal Brownian Motion As a Conformation Of A Polymer Cmentioning
confidence: 99%